1995
DOI: 10.1177/028418519503600215
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic High-Field MR Imaging in Experimental Porcine Acute Pancreatitis

Abstract: The effects of acute pancreatitis on MR imaging signal intensities (SIs) were determined in an experimental study at 1.0 T. Oedematous pancreatitis was induced in 9 piglets and haemorrhagic pancreatitis in II piglets. Each animal served as its own control for MR imaging before and after induction of pancreatitis. TI-weighted spin echo (450/15 ms) and dynamic turbo FLASH (flip angle 8°) sequences were used without contrast medium in testing the stability of the SI measurements. There was no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the iodinated contrast media used in CT are potentially nephrotoxic, especially in the dehydrated patient [3,4]. In our recent study we showed that on non-enhanced MRI piglets with pancreatitis had decreased signal intensities (SI) as compared with healthy animals; however, it could not differentiate reliably between the two types of disease, which corresponds to former studies [5,6]. Gd-DTPA has been shown to have good renal tolerance used in clinical doses, even during dehydration [4,7].…”
mentioning
confidence: 62%
“…However, the iodinated contrast media used in CT are potentially nephrotoxic, especially in the dehydrated patient [3,4]. In our recent study we showed that on non-enhanced MRI piglets with pancreatitis had decreased signal intensities (SI) as compared with healthy animals; however, it could not differentiate reliably between the two types of disease, which corresponds to former studies [5,6]. Gd-DTPA has been shown to have good renal tolerance used in clinical doses, even during dehydration [4,7].…”
mentioning
confidence: 62%